INTERACTIVE CONVENTIONAL STRATEGY INTEGRATED WITH PROJECT-BASED LEARNING TO ENHANCE ENGLISH SPEAKING SKILLS OF FIFTH-GRADE STUDENTS AT SD NEGERI 15 PADANG GENTING - Cecep Maulana; Zulkarnain Sirait (Smart Education, 2025)
Abstract:This study investigates the effectiveness of an interactive conventional teaching strategy integrated with Project-Based Learning (PBL) in enhancing English-speaking skills among fifth-grade students at SD Negeri 15 Padang Genting. A quasi-experimental design was employed with a total sample of 30 students, divided evenly into two groups: an experimental group and a control group. The experimental group was taught using a hybrid approach that combined conventional strategies such as Total Physical Response (TPR), storytelling, and role-play with project-based speaking tasks. The control group received instruction through traditional lecture-based methods. Results revealed a significant improvement in the experimental group’s speaking performance at SD Negeri 15 Padang Genting, with a mean post-test score of 85 and a normalized gain score of 0.64 (moderate–high). In contrast, the control group achieved a mean post-test score of 65 and a gain score of 0.19 (low). An independent samples t-test confirmed that the difference in outcomes was statistically significant (t = 11.45, p < 0.05). Qualitative data from classroom observations and interviews supported these findings, indicating increased student confidence, fluency, and active participation. The study concludes that integrating interactive strategies with PBL is an effective and practical model for improving English-speaking skills in elementary school EFL contexts. Keyword: Interactive Conventional Learning; Project Based Learning; Speaking Skills; Elementary School; Quasi Experiment. Abstrak: Penelitian ini mengkaji efektivitas strategi pembelajaran konvensional interaktif yang diintegrasikan dengan Project-Based Learning (PBL) dalam meningkatkan keterampilan berbicara bahasa Inggris siswa kelas V di SD Negeri 15 Padang Genting. Penelitian ini menggunakan desain kuasi-eksperimen dengan jumlah sampel sebanyak 30 siswa, yang dibagi secara merata menjadi dua kelompok: kelompok eksperimen dan kelompok kontrol. Kelompok eksperimen diajar menggunakan pendekatan hibrida yang menggabungkan strategi konvensional seperti Total Physical Response (TPR), mendongeng, dan bermain peran dengan tugas berbicara berbasis proyek. Sementara itu, kelompok kontrol menerima pembelajaran menggunakan metode ceramah tradisional. Hasil penelitian menunjukkan peningkatan yang signifikan pada kemampuan berbicara siswa kelompok eksperimen di SD Negeri 15 Padang Genting, dengan skor rata-rata post-test sebesar 85 dan skor gain ternormalisasi sebesar 0,64 (kategori sedang–tinggi). Sebaliknya, kelompok kontrol memperoleh skor rata-rata post-test sebesar 65 dan skor gain sebesar 0,19 (kategori rendah). Uji t dua sampel independen mengonfirmasi bahwa perbedaan hasil tersebut signifikan secara statistik (t = 11,45, p < 0,05). Data kualitatif dari observasi kelas dan wawancara mendukung temuan ini, menunjukkan peningkatan kepercayaan diri, kefasihan, dan partisipasi aktif siswa. Studi ini menyimpulkan bahwa integrasi strategi interaktif dengan PBL merupakan model pembelajaran yang efektif dan praktis untuk meningkatkan keterampilan berbicara bahasa Inggris dalam konteks EFL di sekolah dasar. Kata kunci: Pembelajaran Konvensional Interaktif; Project Based Learning; Keterampilan Berbicara ; Sekolah Dasar; Kuasi Eksperimen